Issues of Blood - Laws, Sophie. author. aut Link
XIII, 244 p.
Keywords: An approach to the subject of menstruation which claims that women's feelings about their periods are shaped by men's attitudes and the imposition of their views on women. Sophie Law's research covered men as lovers, fathers, husbands, doctors and "experts".